Light propagation within N95 filtered face respirators: A simulation study for UVC decontamination. Issue 12 (22nd September 2020) - Lilge, Lothar; Manalac, Angelica; Weersink, Madrigal; Schwiegelshohn, Fynn; Young‐Schultz, Tanner; Abdalrhman, Abdallatif Satti; Wang, Chengjin; Ngan, Aldrich; Gu, Frank X.; Betz, Vaughn; Hofmann, Ron
Abstract: This study presents numerical simulations of UVC light propagation through seven different filtered face respirators (FFR) to determine their suitability for Ultraviolet germicidal inactivation (UVGI). UV propagation was modeled using the FullMonte program for two external light illuminations. The optical properties of the dominant three layers were determined using the inverse adding doubling method. The resulting fluence rate volume histograms and the lowest fluence rate recorded in the modeled volume, sometimes in the nW cm −2, provide feedback on a respirator's suitability for UVGI and the required exposure time for a given light source. While UVGI can present an economical approach to extend an FFR's useable lifetime, it requires careful optimization of the illumination setup and selection of appropriate respirators. Abstract : Access to sterile personal protective equipment, in particular for filtered face respirators is critical in the current pandemic for front line healthcare workers. Extended use may be required during supply shortages or due to economic considerations. UVC sterilization can be a cost‐effective technique capable of high throughput. Here we evaluated the suitability of various N95 respirator designs for UV mediated reuse based on the materials utilized. The work determines the respirator fabric's light absorption and scattering coefficients and models the UVC light distributions inside the respirators.